Determination Of The Selling Price Of Auction Land Is Below Standard According To Minister Of Finance Regulation Number 213/PMK.06/2020 - Najiyah, Balqis (International Significance of Notary, 2023)
Abstract: This research is motivated by the problem of many defaults or injuries to promises or defaults on the part of the debtor which then encourages creditors to conduct auctions as a result of which there are often auctions that are not as expected, namely the existence of auctioneers below a reasonable price limit. The purpose of this study is to determine and analyze the importance of determining the selling price of auction land below the standard according to the regulation of the minister of finance 213 / PMK.06 / 2020, the modus operandi of determining the selling price of auction land under the standard set by the regulation of the minister of finance number 213 / PMK.06 / 2020, This research uses normative juridical research methods in the form of a statutory approach (statute approach) and conceptual approach (conceptual approach). Research data is sourced from secondary data sourced from primary legal materials, secondary legal materials and tertiary legal materials which are then analyzed in a qualitative descriptive manner. The results and the first discussion show that the determination of the selling price of auction land in determining the limit value based on the appraisal of the appraiser or the estimator of the estimator, the estimator here is the internal party of the seller or the party appointed by the seller to make an assessment based on a method that can be accounted for. the second, The modus operandi in determining bank auction prices is initially setting a limit value above the liquidation value, but at the time of the auction there is no auction buyer, so at the time of re-auction the limit value price continues to be lowered until a winner / auction buyer is found. Third, the determination of the limit value of the execution auction carried out far below the market price will harm the debtor as explained in article 1365 of the Indonesian Civil Code which discusses Unlawful Acts (PMH). The limit value must be determined first by the seller based on the assessment results of the appraiser where the auction limit value as low as possible must be in accordance with the liquidation value so that the auction office has the authority to reject the auction application submitted by the seller if it is not in accordance with the predetermined standards so as to ensure a sense of justice for the parties. The modus operandi in determining auction prices carried out by banks, first banks use liquidation value as the limit value, is, banks initially set the limit value above the liquidation value but at the time of auction there is no auction buyer. The determination of the execution auction limit value that is carried out far below the market price will harm the debtor as explained in article 1365 of the Indonesian Civil Code which discusses Unlawful Acts (PMH)Keywords: Standard, Auction Land, Minister of Finance Regulation Number